2016
DOI: 10.1016/j.ssresearch.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Home sweet home? Home physical environment and inflammation in children

Abstract: The home environment includes important social and physical contexts within which children develop. Poor physical home environments may be a potential source of stress for children through difficult daily experiences. Using a sub-sample from the Los Angeles Family and Neighborhood Survey (N = 425), we consider how the home physical environment affects stress-related immune system dysregulation in children ages 3–18 years. Results indicated that children in poorer quality homes had higher inflammation (measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 74 publications
(110 reference statements)
1
28
1
2
Order By: Relevance
“…In contrast, when housing conditions are unfavorable, potential benefits associated with favorable conditions may be forfeited and replaced with a wide range of adverse outcomes (Evans, ; Ferguson, Cassells, MacAllister & Evans, ; Suglia, Duarte & Sandel, ). Research has linked poor housing conditions to various health conditions (Baranwal, Baranwal & Roy, ; Cattaneo, Galiani, Gertler, Martinez & Titiunik, ; Holt, Theall & Rabito, ; Schmeer & Yoon, ), diminished overall health status (Dush, Schmeer & Taylor, ), and hospital admissions (Kelly et al., ) among child residents. There is also evidence of associations between housing conditions and other aspects of child development, including cognitive, emotional, and behavioral functioning (Coldwell, Pike & Dunn, ; Coley, Kull, Leventhal & Lynch, ; Coley, Lynch & Kull, ; Deater‐Deckard et al., ; Dumas et al., ; Jocson & McLoyd, ; Pike, Iervolino, Eley, Price & Plomin, ; Solari & Mare, ; Vernon‐Feagans, Willoughby & Garrett‐Peters, ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, when housing conditions are unfavorable, potential benefits associated with favorable conditions may be forfeited and replaced with a wide range of adverse outcomes (Evans, ; Ferguson, Cassells, MacAllister & Evans, ; Suglia, Duarte & Sandel, ). Research has linked poor housing conditions to various health conditions (Baranwal, Baranwal & Roy, ; Cattaneo, Galiani, Gertler, Martinez & Titiunik, ; Holt, Theall & Rabito, ; Schmeer & Yoon, ), diminished overall health status (Dush, Schmeer & Taylor, ), and hospital admissions (Kelly et al., ) among child residents. There is also evidence of associations between housing conditions and other aspects of child development, including cognitive, emotional, and behavioral functioning (Coldwell, Pike & Dunn, ; Coley, Kull, Leventhal & Lynch, ; Coley, Lynch & Kull, ; Deater‐Deckard et al., ; Dumas et al., ; Jocson & McLoyd, ; Pike, Iervolino, Eley, Price & Plomin, ; Solari & Mare, ; Vernon‐Feagans, Willoughby & Garrett‐Peters, ).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research has linked children's health to the condition of their domiciles (Baranwal et al., ; Cattaneo et al., ; Dush et al., ; Holt et al., ; Schmeer & Yoon, ). In addition to compromised health, Schmeer and Yoon () recently found that home environments that are kept in poor condition can constitute a significant source of psychosocial stress.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations